A female case report of LGMD2B with compound heterozygous mutations of the DYSF gene and asymptomatic mutation of the X-linked DMD gene - Cao, Xiaojie; Zeng, Li; Lu, Zhijie; Fan, Jin; Tan, Song; Zhang, Mingjie; Yin, Zegang (Frontiers in Neurology, 2023)
We report a female case complaining of the weakness of lower limbs which is finally diagnosed as limb-girdle muscular dystrophy 2B (LGMD2B) with compound heterozygous mutations of the DYSF gene. Meanwhile, this woman is an asymptomatic carrier with mutation of the X-linked DMD gene. A 31-year-old Chinese woman presented with a chief complaint of lower limb weakness. The electromyography, muscle MRI and muscle biopsy suggested the chronic myogenic injury with dysferlin deletion. As a genetic testing result, compound heterozygous G-to-T base substitution at position 5497 in exon 49 of the DYSF gene, leading to a codon change from glutamic acid to termination codon at position 1833, along with a heterozygous C-to-G base change at position 4638+8 in intron 42 of the DYSF gene with consequence of splice, which has never been reported, were identified as candidate causative mutations. Unfortunately, DMD gene mutation c.3921+12A>G of the DMD gene on the X chromosome was also found in this patient. Finally, the patient was diagnosed as LGMD2B clinically and genetically. The last two years, the patient lower limb weakness got a little worse resulting in walking distance even shorter than before. Fortunately, during the follow-up, her little son has not shown slowness or limitation of movement. Genetic testing by next generation sequencing confirmed the final diagnosis of LGMD2B and identified the novel compound heterozygous variants in DYSF gene, which is of great significance to accurate diagnosis of genetically coded diseases. Much attention must be paid in clinic to the hereditary neuromuscular diseases with multiple pathogenic gene mutations. Genetic counseling and clinical follow-up are the priorities in the future and promising treatments are also worth exploring.